L'enseignement de questions socialement vives en Biélorussie : enjeux et spécificités - Anna Zadora (Université de Provence, 2016)
The teaching of history in the context of post-Soviet Belarus had a very specific evolution. During Soviet period, the teaching of history was submitted to the purposes of legitimation of the political system, and teaching was a mechanical memorization of dogmatic truths, but not aiming at the skills development and critical thinking. Under perestroika, history has been requisitioned to legitimize the political and identity project of the independent Belarus. The school history became an independent discipline, first textbooks were written. For the first time, the educational goals of forming conscious citizens, the awakening of critical thinking were discussed. In the mid-1990s, a return to the Soviet legacy has happened in Belarus. Textbooks of perestroika were replaced with textbooks defending Soviet heritage. The aims of education are again subjected to the legitimization of a specific political regime through mechanical memorization in the framework of education that erases controversial topics, or offers partial treatment of controversial issues and does not aim the development of skills.